Pengaruh Kombinasi Pemangkasan Akar dan Sumber Inokulum Ektomikoriza Terhadap Pertumbuhan Bibit Melinjo (Gnetum gnemon) - Arum Sekar Wulandari; . Supriyanto; Hannum Wulan Febrianingrum (Institut Pertanian Bogor, 2015)
Root pruning technique may improve new lateral growth. The purposes of this research are to analyse the combined effect of root pruning and inoculum ectomycorrizal types on the growth of gnetum seedling (Gnetum gnemon). This research using split plot design. The source of ectomycorrizhal inoculum as main plot consist of 3 types: control, infected seedling of ectomycorrhizal, and soil inoculum. The root pruning level as sub plot also consist of 3 types: 0, 30, and 50%. Observation is conducted on month 5th and 6th after treatment. The result of this research indicates that root pruning technique on 7 month seedling able to enhance melinjo seedling’s growth and increase ectomycorrhizal colonization (Scleroderma spp.) after 6 months observation. The source of inoculum was able to enhance ectomyrorrhizal colonization but had no significant to gnetum seedling’s growth on month 6th after treatment. Interaction between root pruning 30% and fungal inoculation with soil inoculum source can improve gnetum seedling growth.